PENGARUH KEMAMPUAN PIMPINAN TERHADAP EFEKTIVITAS KERJA POLISI SATLANTAS POLRES KUTAI KERTANEGARA - Siswanto, Gatot (PREDIKSI, 2012)
Effectiveness of the organization is essentially a ballad in the individual effectiveness in carrying out duties in accordance with the positions and their respective roles within the organization. To measure the effectiveness of administrative organizations as well as government organizations, is not easy. Probably much easier to measure the effectiveness of business organizations, whose main objective is to find provit money's worth (material). The purpose of the administrative organization of government very broad and abstract, which is usually expressed implicitly to serve the public interest. This is something that is very broad, abstract and very difficult to measure.